Análise da relação dos custos de agência com o conservadorismo contábil e com as práticas de governança corporativa das empresas de capital aberto listadas na BM&FBOVESPA - Medeiros, David Nunes de (2017)
This research had the objective of analyzing the relationship between agency cost and accounting conservatism and with the corporate governance practices of public companies listed on BM&FBOVESPA. To achieve the objective, data from the annual standardized financial statements and reference forms were used. The survey sample comprises 239 nonfinancial companies listed on the BM&FBOVESPA in the period from 2010 to 2015 that were part of the latest IBrX100 released each year. The model of Khan and Watts (2009) was used to calculate the C-Score, a metric that indicates how conservative a firm was in a given year. The Corporate Governance Practices used were the Duality of functions of the CEO and Chairman, Independence of the Board of Directors, Size of the Board of Directors, Remuneration of the Board of Directors and participation in the New Market. The agency cost was calculated based on Ang, Cole and Lin (2000), Singh and Davidson (2003) and McKnight and Weir (2009), using the variables denominated in this research as Asset Turning and Cost Inefficiency. Six hypotheses were tested based on the existing literature on the subjects discussed. Data were estimated by quantum regression, and hypotheses were tested in five quantiles of the distribution, aiming to collect more details about the influence of each variable studied in the sample. The results of the research showed that when agency costs were analyzed through the Asset Turnover, Accounting Conservatism was determinant for the reduction of these costs, proving to be an important tool for the management of the company, corroborating with Chi, Liu and Wang (2009). On the other hand, adherence to Corporate Governance Practices was not significantly important in reducing agency costs from the inefficient use of revenues to generating assets. When agency cost was measured by the relation between Administrative Expenses and Total Revenues, only the fact that it was in the Novo Mercado was determinant for the reduction of these costs.